Undercover infrastructure: Dual-use arctic satellite ground stations - Gregory Falco; Nicolò Boschetti; Ioannis Nikas (Centre for International Governance Innovation (CIGI), 2024)
Private companies are launching more rockets and satellites into space than ever before, increasing the amount of space assets and infrastructure for both civilian and military use. While these dual-use technologies, such as satellite communications, provide a wide range of essential services, they can also become military targets, posing significant security risks. This paper looks at satellite ground stations in the Arctic, how they are used, and how they can be protected in the face of growing geopolitical tensions among major powers such as China, Russia and the United States.
Keywords: 330